"If you Build it with them, they will come": What makes a supermarket intervention successful in a food desert?. Issue 3 (27th February 2019) - Brinkley, Catherine; Glennie, Charlotte; Chrisinger, Benjamin; Flores, Jose
Abstract : Using 71 planned supermarket interventions in food deserts, this study assesses the interplay between regional geography, management models, policy drivers, financing, and timing. We find that community engagement and cooperative management models are important factors to opening and sustaining a new store, contributing to subsequent improvements in the foodscape, built environment, and diet‐related health. Findings show that none of the nonprofit or community‐driven stores have closed whereas nearly half of the commercial‐driven and one third of government‐driven cases resulted in canceled plans or closed stores. Our research suggests community engagement is a critical component of effective policies for healthy food access. Future studies may wish to include measurements of community engagement with their case studies to better situate explanatory findings.